Spotlight on nilotinib in the treatment of chronic myelogenous leukemia - Harnicar S (Dove Medical Press, 2014)
Stephen Harnicar, Sherry Mathew Department of Pharmacy, Memorial Sloan Kettering Cancer Center, New York, NY, USA Abstract: Nowhere has targeted therapy been more successful in the hematologic malignancy arena than chronic myelogenous leukemia (CML). By targeting the BCR–ABL fusion oncogene, the introduction of tyrosine-kinase inhibitors (TKIs) has dramatically improved the outcomes of this disease. Nilotinib is a second-generation TKI that initially gained approval for the treatment of imatinib-resistant or -intolerant disease for patients with chronic or accelerated-phase CML. Investigation in the first-line setting also demonstrated efficacy, and expanded nilotinib’s approval to include therapy for patients with treatment-naïve chronic-phase CML. Data also exist for blast-phase disease, which allows nilotinib to be an option for all phases. Nilotinib’s place in therapy is continuously being expanded by research in novel areas, such as post-hematopoietic stem cell transplants for prevention of relapse and in the pediatric arena. With multiple TKIs now approved for the treatment of CML, delineating the pharmacologic distinctions of nilotinib is an asset when determining therapy. By understanding the pharmacokinetics and dependence on hepatic metabolism of nilotinib, the clinician can manage the potential toxicities, interactions, and unique dosing of this drug. The recognition of mechanisms of resistance, patient adherence, and cost-effectiveness are similarly significant considerations. Actively integrating these various specifics will allow clinicians to optimize nilotinib therapy for the CML patient. Keywords: nilotinib, chronic myelogenous leukemia, CML, tyrosine-kinase inhibitor, TKI